2020
DOI: 10.1177/0886260520922342
|View full text |Cite
|
Sign up to set email alerts
|

Examining Men’s Experiences of Abuse From a Female Intimate Partner in Four English-Speaking Countries

Abstract: This qualitative study explores the experiences of men who self-report victimization from a female intimate partner in four English-speaking countries. Forty-one men who reported any type of intimate partner abuse (IPA) from a female partner were recruited via targeted advertising in Australia, Canada, the United Kingdom, and the United States. Twelve online focus groups were conducted across countries using a phenomenologically informed design. Thematic analysis was carried out from an inductive and realist e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(57 citation statements)
references
References 27 publications
3
54
0
Order By: Relevance
“… Note. The same table appears in other articles published with these data (Dixon et al, in press; Lysova et al, in press). …”
Section: Methodsmentioning
confidence: 69%
See 1 more Smart Citation
“… Note. The same table appears in other articles published with these data (Dixon et al, in press; Lysova et al, in press). …”
Section: Methodsmentioning
confidence: 69%
“…For this study, we analyzed responses to Question 4 to provide an in-depth focus on men’s help-seeking that involved a CJS response. The other questions are the focus of other publications (Dixon et al, in press; Douglas et al, 2018; Lysova et al, in press).…”
Section: Methodsmentioning
confidence: 99%
“…We are aware because of the length of this process there is new evidence which could be assimilated into this IMMS. Three multi-country studies by the same research team have been published in 2020 [37][38][39].. One of these new studies reenforces the findings of our IMMS on help seeking by male victims and service provision [37]. The second study specifically examines male victims experiences of the criminal justice system and this would add new material to our IMMS [38].…”
Section: Strengths and Limitationsmentioning
confidence: 95%
“…The second study specifically examines male victims experiences of the criminal justice system and this would add new material to our IMMS [38]. The final study focuses on male victims experiences of female perpetrated violence [39]. In an ideal world we would update this IMMS but we are confident that the evidence summary and conclusions still stands in 2020.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Large sample quantitative studies that perforce homogenize men's experiences can make it appear as though their rates of victimization are similar to women, but claims of symmetry in GBV are highly disputed as the large data sets used to demonstrate symmetry often lack the complexity of measurement or depth of context required to compare men's experiences to women's effectively (Anderson, 2005; Felson & Cares, 2005; Gavey, 2019; Harris, 2012; Michalski, 2005; Morris & Ratajczak, 2019; Stemple, Flores, Ilan, & Meyer, 2017; Stemple & Meyer, 2014). That said, recent research with small samples has demonstrated that violence inflicted on men by female partners is often quite severe (Allen‐Collinson, 2011; Archer, 2002; Dixon et al., 2020; Migliaccio, 2001), and that the longstanding argument that women only or usually commit violence in self‐defense may not be empirically supported (Felson & Cares, 2005; Sarantakos, 2004).…”
Section: Theories Relating Men Masculinity and Gbvmentioning
confidence: 99%